2001
DOI: 10.1177/107906320101300305
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sexual Offenders Who Are in Categorical Denial: A Pilot Project

Abstract: This paper describes an approach to treatment for sexual offenders who are in categorical denial. Other efforts to have them, at least partially, admit responsibility had failed and they were to be released from prison without any treatment. Evidence that suggests denial is not predictive of risk and that treatment may reduce the risk of these offenders is reviewed. Essentially, this paper offers a possible approach to dealing with these intractable deniers which, it is suggested, is better than not trying to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 23 publications
4
59
0
6
Order By: Relevance
“…We did not have access to data on participation in sex offender treatment and, therefore, were unable to examine it as a potential moderator of the relationship between denial and recidivism. Given that denial appears to decrease over the course of treatment (Barbaree 1991;Marshall et al 2001), we may have found different results had we considered participation in treatment. In terms of the nature of our denial variable, we used a dichotomous variable, whereas some researchers have conceptualized denial as a multidimensional construct (Schneider and Wright 2001).…”
Section: Discussionmentioning
confidence: 70%
“…We did not have access to data on participation in sex offender treatment and, therefore, were unable to examine it as a potential moderator of the relationship between denial and recidivism. Given that denial appears to decrease over the course of treatment (Barbaree 1991;Marshall et al 2001), we may have found different results had we considered participation in treatment. In terms of the nature of our denial variable, we used a dichotomous variable, whereas some researchers have conceptualized denial as a multidimensional construct (Schneider and Wright 2001).…”
Section: Discussionmentioning
confidence: 70%
“…Laws [30, S. 174] nennt den Ausschluss von Leugnern aus der Behandlung "unethisch und professionell unverantwortlich" und argumentiert, es gebe keine Belege dafür, dass das Leugnen eine erfolgreiche Behandlung verhindere. Marshall et al [36] haben ein Pilotprogramm zur Behandlung von leugnenden Sexualstraftä-tern beschrieben.…”
Section: Formenunclassified
“…Certains auteurs [12,14] ont pointé que les é tudes de Hanson ne comprenaient qu'un trè s faible nombre de personnes pré sentant un dé ni complet des faits et que ce que les auteurs appelaient dé ni pouvait recouvrir diffé rents degré s de minimisations. Nunes et al [18] ont montré que le lien entre ré cidive et dé ni des faits é tait plus complexe.…”
Section: De´ni Et Re´cidiveunclassified
“…Marshall et al le nomment « categorical denial » [14], Schneider et Wright [25], « full denial », ou encore « absolute denial » pour Schlank et Shaw [23]. Ces termes recouvrent tous un refus caté gorique de reconnaître la moindre participation personnelle aux faits incriminé s. La litté rature souligne bien qu'il ne s'agit pas ici de minimisation ou de reconnaissance partielle, mais bel et bien d'un dé ni opposé à une accusation, puis à une condamnation.…”
Section: Introductionunclassified